'Marginalised malignancies': A qualitative synthesis of men's accounts of living with breast cancer. (January 2016) - Quincey, Kerry; Williamson, Iain; Winstanley, Sue
Abstract: Rationale: Breast cancer in men is a rare, under-researched illness frequently overlooked within both clinical and third-sector healthcare systems. Increased prevalence and high profile awareness-raising, advocacy and activism around breast cancer in women has led to pervasive feminisation of the disease, prompting a misperception of breast cancer as a women-only illness. This deters men from seeking medical attention, professional and social support, and increases sensitivity to body image concerns. Methods: Drawing on the principles of critical health psychology, we offer an interpretive and evaluative qualitative synthesis of existing academic literature in the field, and reveal how the marginalisation of men with breast cancer poses a host of psychosocial and psychosexual difficulties for patient-survivors beyond the primary cancer challenge at all stages of the illness trajectory. Results: We discuss how identities, masculinities, coping responses and resources, and relationships are often affected, and demonstrate how current approaches to breast cancer serve to isolate men who develop the illness, potentially alienating and emasculating them. Conclusion: Our analysis integrates and enhances the findings of the original papers through more theorised considerations of stigma, masculinity and marginalisation. Further, we briefly consider some of the ways men's experiences diverge and converge with women's accounts, and discuss the importance of re-appraising 'pink ribbon culture' for both men and women. We conclude with some recommendations for advocacy and intervention in professional and lay contexts. Highlights: This synthesis positions breast cancer in men as a marginalised malignancy. Current breast cancer care and support overlooks men's psychosocial needs. Men with breast cancer experience 'othering' but also engage in 'self-stigma'. Illustrates the centrality of masculinity in men's experiences of breast cancer. Subtle rather than radical modifications are advised for improved future care.